Pemetaan Tesis dalam Aliran-Aliran Filsafat Hukum dan Konsekuensi Metodologisnya - Mahrus Ali (Jurnal Hukum IUS QUIA IUSTUM, 2017)
The main problems in this research: first, how are the theses constructed by the schools in legal philosophy? Second, what are the methodological consequences that emerge dut the different theses of each school in legal philosophy? This research was a normative legal research. The result of the research concluded, first, every law school that exists in legal philosophy has different thesis from one to the other. The thesis of natural law school is the thesis of morality and normativity. Legal realism separates law and moral, and puts more importance on social facts. The thesis of Kelsen's pure theory of law is a synthesis of the thesis of natural law and empirical positivism/legal realism. The thesis of American Sociological Jurisprudence is a synthesis of the legal positivism and the school of history; it separates law and morals as well as the unity between law and fact. Meanwhile, the thesis of utilitarianism is the separation between law and moral as well as the unity between law and fact. Second, the thesis differences in the schools of legal philosophy have consequences on the methodology that is used.